2008
DOI: 10.1021/pr7007658
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Identification of the Outer Membrane Protein OmcA−MtrC Interaction Network in Shewanella oneidensis MR-1 Cells Using Novel Hydrophobic Chemical Cross-Linkers

Abstract: Outer membrane (OM) cytochromes OmcA (SO1779) and MtrC (SO1778) are the integral components of electron transfer used by Shewanella oneidensis for anaerobic respiration of metal (hydr)oxides. Here the OmcA-MtrC interaction was identified in vivo using a novel hydrophobic chemical cross-linker (MRN) combined with immunoprecipitation techniques. In addition, identification of other OM proteins from the cross-linked complexes allows first visualization of the OmcA-MtrC interaction network. Further experiments on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
87
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 70 publications
(89 citation statements)
references
References 45 publications
(84 reference statements)
1
87
1
Order By: Relevance
“…Despite their great potential, current XL-MS studies that have aimed to identify cross-linked peptides have been mostly limited to in vitro cross-linking experiments, with few successfully identifying protein interaction interfaces in living cells (24,25). This is largely because XL-MS studies remain challenging due to the inherent difficulty in the effective MS detection and accurate identification of cross-linked peptides, as well as in unambiguous assignment of cross-linked residues.…”
mentioning
confidence: 99%
“…Despite their great potential, current XL-MS studies that have aimed to identify cross-linked peptides have been mostly limited to in vitro cross-linking experiments, with few successfully identifying protein interaction interfaces in living cells (24,25). This is largely because XL-MS studies remain challenging due to the inherent difficulty in the effective MS detection and accurate identification of cross-linked peptides, as well as in unambiguous assignment of cross-linked residues.…”
mentioning
confidence: 99%
“…The use of XL-MS to study protein structures and interactions directly from living cells was first demonstrated on the bacterial system Shewanella oneidensis, where new details on the membrane protein electron transport machinery used during anaerobic respiration were discovered (14). More recently XL-MS has been applied to E. coli cell lysates (15,16) as well as intact E. coli cells (17,18).…”
mentioning
confidence: 99%
“…Prior to conducting the Ig-RFM experiments, the specificity of each polyclonal antibody (i.e., anti-OmcA and anti-MtrC) for OmcA or MtrC was verified by Western blot analysis as described previously (24,28). Proteins were resolved by both denaturing and nondenaturing polyacrylamide gel electrophoresis (PAGE).…”
mentioning
confidence: 99%
“…Anti-OmcA bound exclusively to OmcA, anti-MtrC bound exclusively to MtrC, and neither antibody showed crossreactivity with the other cytochrome. Antibody specificities of anti-OmcA and anti-MtrC were also validated by immunoblot analysis of S. oneidensis whole-cell lysate (28).…”
mentioning
confidence: 99%